Genetic diversity of Prosopis juliflora in the state of Qatar and its valuable use against postharvest pathogen of mango fruits - Iman Saleh (14152878) (2022)
Mango (Mangifera indica) is the second most internationally traded tropical fruit in the world. The fruit has high nutritional value. Its susceptibility to postharvest diseases and chill injuries increases its storage cost and put stress on exploring natural products that can increase its shelf-life. Our team has previously described Prosopis juliflora water-soluble leaf ethanolic (PJ-WS-LE) extract with fungicidal effectiveness against spoiling fungi. The present study explores P. juliflora genetic diversity in the state of Qatar and the antifungal effectiveness of the leaf extract of plants collected from different locations. The study also evaluates PJ-WS-LE extract efficacy against Alternaria. alternata and Colletotrichum gloeosporioides inoculated in mango samples and the power of the extract as coating material. P. juliflora samples collected from six different locations showed genetic and antimicrobial effectiveness similarities. They showed also similarity to the sequence representing P. juliflora 18S ribosomal RNA partial sequence, accession number JX139107.1 originated from India. PJ-WS-LE extract (8 mg/ml) has 80% efficacy in controlling A. alternata in mango and it lowers C. gloeosporioides disease severity by 53.4%. PJ-WS-LE extract (8 mg/ml) embedded in 1% chitosan maintained mango quality for 5 weeks. In vivo results of PJ-WS-LE extract highlights the potentials of the extract as chemical fungicides replacement. Other Information Published in: Scientific Reports License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1038/s41598-022-14871-x